Evaluation of Serum 8-Hydroxy-Deoxyguanosine, Interleukin-6 and Interleukin-7 in Type 2 Diabetic Iraqi Females - Shakir F.T. Alaaraji (Journal of Global Pharma Technology, 2018)
Background: Diabetes a devastating disease throughout the world. It is related with numerous mechanisms, the first one is oxidative stress. Oxidative stress shows an main role in the pathogenesis and the complications of disease. Objective: The aim of the current study was to measure five important factors in patients with type 2 diabetic patients (the amount of 8-OHDG, IL-6, IL-7, Blood Pressure, and Pulses). These factors were surveyed in type 2 diabetic patients to compare with healthy controls and study the association among 8-OHDG in diabetic patients with other parameters in the study. Materials & Methods: Population consists of 51 patients diagnosed with T2DM and a control group of 31 healthy people. 8-OHDG, interleukin-6, interleukin-7 and blood pressure levels were assessed in all subjects. Results: Levels of five markers in serum (8-OHDG, IL-6, IL-7, Blood Pressure, and Pulses) were significantly greater inT2DM group compared to control group. The receiver operator curve (ROC) analysis of the forthcoming variations revealed the descending order of serum IL-7 (0.975), IL-6 (0.972), and 8-OHDG (0.899), Conclusion: the study recommends that 8-OHDG level in type 2 diabetic patients may be a useful marker of DNA damage. So we should monitor this variable level in blood continuously to maintain their health.Keywords: ● T2DM ● Interleukin-6 ● Interleukin-7 ●8-OHDG.